서비스로봇의 신뢰성 향상을 위한 OPRoS 기반 Fault-tolerance 기법 - 안희준; 이동수; 안상철 (제어·로봇·시스템학회, 2010)
For commercial success of emerging service robots, the fault tolerant technology for system reliability and human safety is crucial. Traditionally fault tolerance methods have been implemented in application level. However, from our studies on the common design patterns in fault tolerance, we argue that a framework-based approach provides many benefits in providing reliability for system development. To demonstrate the benefits, we build a framework-based fault tolerant engine for OPRoS (Open Platform for Robotic Services) standards. The fault manager in framework provides a set of fault tolerant measures of detection, isolation, and recovery. The system integrators choose the appropriate fault handling tools by declaring XML configuration descriptors, considering the constraints of components and operating environment. By building a fault tolerant navigation application from the non-fault-tolerant components, we demonstrate the usability and benefits of the proposed framework-based approach.